2015
DOI: 10.1080/03601234.2015.1058097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, pH and NaCl content onin vitroputrescine and cadaverine production through the growth ofSerratia marcescensCCM 303

Abstract: The aim of this study was to evaluate the combined effect of temperature (10, 20 and 37°C), pH (4, 5, 6, 7 and 8), and NaCl content (0, 1, 3, 4, 5 and 6% w/v) on the growth and putrescine and cadaverine production of Serratia marcescens CCM 303 under model conditions. The decarboxylase activity of S. marcescens was monitored in broth after cultivation. The cultivation medium was enriched with selected amino acids (ornithine, arginine and lysine; 0.2% w/v each) serving as precursors of biogenic amines. Levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Similar effects were described also for Bifidobacteria ( Lorencová et al, 2014 ). The hypothesis of this possible enhancing effect on the BA production of NaCl has been found by some authors in the essential role of Na + ion in the sodium/proton antiport system through which H + ions are removed from the cell ( Pereira et al, 2009 ; Buňková et al, 2011 ; Lorencová et al, 2014 ; Bubelová et al, 2015 ).…”
Section: Environmental Factors Influencing Biogenic Amine Formationmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar effects were described also for Bifidobacteria ( Lorencová et al, 2014 ). The hypothesis of this possible enhancing effect on the BA production of NaCl has been found by some authors in the essential role of Na + ion in the sodium/proton antiport system through which H + ions are removed from the cell ( Pereira et al, 2009 ; Buňková et al, 2011 ; Lorencová et al, 2014 ; Bubelová et al, 2015 ).…”
Section: Environmental Factors Influencing Biogenic Amine Formationmentioning
confidence: 97%
“… Bubelová et al (2015) studied the production of putrescine and cadaverine in relation to temperature in Serratia marcescens . They found that the maximum amount of these two BAs was reached at 20–30°C.…”
Section: Environmental Factors Influencing Biogenic Amine Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…During manufacturing, pH plays a leading role, promoting decarboxylase activity. In these products, where mainly LAB cultures are employed to carry on fermentation, acidification can limit or stress BAs production [93]. Another factor that diminishes BAs formation by microorganisms is the presence of salt.…”
Section: Biogenic Amines In Processed Meatsmentioning
confidence: 99%
“…Our previous study with this cured meat found correlations between its physicochemical characteristics and oxidative state, where a w and NaCl content were highly important (Rosario et al ., 2020). In addition, these characteristics are directly involved in the microbiota present in the meat product and their BAs production, as evidence suggests that they affect the activity of amino acid decarboxylases (Bozkurt et al ., 2004; Bubelová et al ., 2015). Therefore, the present study uses chemometrics to unravel the intrinsic correlations between the BDL microbiota and BAs content as influenced by the cured‐meat physicochemical characteristics.…”
Section: Introductionmentioning
confidence: 99%